Insights into Sexism: Male Status and Performance Moderates Female-Directed Hostile and Amicable Behaviour. - Michael M Kasumovic; Jeffrey H Kuznekoff (PLoS ONE, 2015)
Gender inequality and sexist behaviour is prevalent in almost all workplaces and rampant in online environments. Although there is much research dedicated to understanding sexist behaviour, we have almost no insight into what triggers this behaviour and the individuals that initiate it. Although social constructionist theory argues that sexism is a response towards women entering a male dominated arena, this perspective doesn't explain why only a subset of males behave in this way. We argue that a clearer understanding of sexist behaviour can be gained through an evolutionary perspective that considers evolved differences in intra-sexual competition. We hypothesised that female-initiated disruption of a male hierarchy incites hostile behaviour from poor performing males who stand to lose the most status. To test this hypothesis, we used an online first-person shooter video game that removes signals of dominance but provides information on gender, individual performance, and skill. We show that lower-skilled players were more hostile towards a female-voiced teammate, especially when performing poorly. In contrast, lower-skilled players behaved submissively towards a male-voiced player in the identical scenario. This difference in gender-directed behaviour became more extreme with poorer focal-player performance. We suggest that low-status males increase female-directed hostility to minimize the loss of status as a consequence of hierarchical reconfiguration resulting from the entrance of a woman into the competitive arena. Higher-skilled players, in contrast, were more positive towards a female relative to a male teammate. As higher-skilled players have less to fear from hierarchical reorganization, we argue that these males behave more positively in an attempt to support and garner a female player's attention. Our results provide the clearest picture of inter-sexual competition to date, highlighting the importance of considering an evolutionary perspective when exploring the factors that affect male hostility towards women.